A mutant of Pseudoalteromonas carrageenovora arylsulfatase with enhanced enzyme activity and its potential application in improvement of the agar quality. (1st August 2020) - Zhu, Yanbing; Liang, Meifang; Li, Hebin; Ni, Hui; Li, Lijun; Li, Qingbiao; Jiang, Zedong
Highlights: Mutant arylsulfatase K253Q was obtained by error-prone PCR based directed evolution. K253Q increased the desulfation activity against the sulfate groups in agar. K253Q has a great potential for application in improvement of the agar quality. Abstract: Enzymatic desulfation using arylsulfatase provides an attractive approach to improve agar quality. We have previously characterized a functional arylsulfatase from Pseudoalteromonas carrageenovora. To further improve its enzymatic performance, we isolated a mutant arylsulfatase of K253Q with improved enzyme activity from a random mutant library. Compared to wild-type arylsulfatase (WT), K253Q showed 33% increase in enzyme activity, with optimal temperature and pH of 55 °C and 8.0, respectively. K253Q demonstrated better substrate binding ability with lower Km value. Structure analysis indicated that a combination of the additional hydrogen bond and the enhanced substrate binding affinity could account for the improved enzyme activity of K253Q. K253Q exhibited about 54% sulfate removal against agar, resulting in additional 8% increase in 3, 6-AG content and 20% increase in gel strength compared to WT. Scanning electron microscopy showed that K253Q treatment led to a stronger crosslinking structure of agar.